2015
DOI: 10.5565/rev/elcvia.680
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Segmentation of Optic Disc in Eye Fundus Images: A Survey

Abstract: Optic disc detection and segmentation is one of the key elements for automatic retinal disease screening systems. The aim of this survey paper is to review, categorize and compare the optic disc detection algorithms and methodologies, giving a description of each of them, highlighting their key points and performance measures. Accordingly, this survey firstly overviews the anatomy of the eye fundus showing its main structural components along with their properties and functions. Consequently, the survey review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…The entropy of different patch images obtained by the sliding window technique was analyzed using recursive steps in their study [6]. Allam et al focused on this subject with three categories: (a) using the size, color, and brightness characteristics (b) forecasting the convergence point of the vessels (c) template matching [7]. Lalonde detected OD by template matching based on pyramidal decomposition and Hausdorff in low-resolution fundus images [12].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The entropy of different patch images obtained by the sliding window technique was analyzed using recursive steps in their study [6]. Allam et al focused on this subject with three categories: (a) using the size, color, and brightness characteristics (b) forecasting the convergence point of the vessels (c) template matching [7]. Lalonde detected OD by template matching based on pyramidal decomposition and Hausdorff in low-resolution fundus images [12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The detection of glaucoma eye disease is related to tracing the changes in the optic cup. This region must be detected in the retinal image [6] due to it enables ophthalmologists to mitigate the effects of these diseases [7].…”
Section: Introductionmentioning
confidence: 99%
“…It is the brightest part of a healthy eye and is seen as a bright yellowish or white region in a fundus image [7]. Exudates have similar values, so it is important to eliminate optic disk (OD) from the retinal image; the removal of OD is necessary.…”
Section: B the Detection Of Optic Diskmentioning
confidence: 99%
“…Diabetic retinopathy particularly is a major sight-threatening complication caused by diabetes mellitus. Diabetes harmfully affects the retina (diabetic retinopathy), as well as the kidneys (diabetic nephropathy) and the nervous system (diabetic neuropathy) as stated by Patton et al (2006) and Allam et al (2015). Also, WHO (2016) reported that 2.6% of global blindness could be attributed to diabetic retinopathy, in which the number of people with diabetes had risen from 108 million in 1980 to 422 million in 2014.…”
Section: Introductionmentioning
confidence: 99%